2022
DOI: 10.1159/000525766
|View full text |Cite
|
Sign up to set email alerts
|

Viral Clearance with Neutrophil Recovery in a Patient with Active COVID-19 Infection and Refractory Acute Myeloid Leukemia Who Underwent Successful Reinduction with Cytarabine/Idarubicin

Abstract: Administering myelosuppressive chemotherapy to patients with aggressive malignant hematologic disorders typically poses serious infectious complications, which can be exacerbated by the presence of active COVID-19 infection. We report on a case of a successfully treated fit elderly woman with refractory acute myeloid leukemia (AML) who also had mild COVID-19 infection and detectable viral load at the time she was found to have recurrent disease. Prior to initiation of reinduction treatment with cytarabine/idar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…On 5 April 2022, the FDA announced that it is no longer authorized to treat COVID-19 in any U.S. region due to increases in the proportion of COVID-19 cases caused by the Omicron BA.2 sub-variant [ 97 ]. Dean et al reported one case of a successfully treated patient with acute myeloid leukemia and mild COVID-19 infection, who received antiviral therapy with remdesivir and sotrovimab [ 98 ]…”
Section: Sotrovimab (Xevudy)mentioning
confidence: 99%
“…On 5 April 2022, the FDA announced that it is no longer authorized to treat COVID-19 in any U.S. region due to increases in the proportion of COVID-19 cases caused by the Omicron BA.2 sub-variant [ 97 ]. Dean et al reported one case of a successfully treated patient with acute myeloid leukemia and mild COVID-19 infection, who received antiviral therapy with remdesivir and sotrovimab [ 98 ]…”
Section: Sotrovimab (Xevudy)mentioning
confidence: 99%